(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
Objectives: This study aims to identify the directions of Sufi allusion in modern Arabic Poetry through uncovering its meanings, interpreting it, and elucidating its textual references; and it sheds light on eleven poets from both the Eastern and Western Arab worlds who have skillfully adopted these elements. Methods: The study employs semiotics of interpretation as a guiding method, which is suitable for addressing the suggestive nature of Sufi allusion and the unique figurative capacity of poetic texts to trace, interpret, and articulate the directions of these allusions. Results: The study concludes that the Sufi allusion, in its lexical and semantic structure, is broader and more precise than both of the Sufi symbol and terminology, encompassing them within itself. The allusion operates across four directions: it retains its mystical dimension in the first, adopts a political and social orientation in the second, explores existential themes with an erotic tone in the third, and takes on cultural and artistic aspects in the fourth. Conclusions: The study recommends that researchers should focus on examining the Sufi allusion through the lens of interpretive semiotics, leveraging its methodology to strengthen the connection between modern literature and Arab heritage, together with contemporary reading approaches.